How entrepreneurs' Zhong-yong thinking improves new venture performance: The mediating role of guanxi and the moderating role of environmental turbulence. Issue 2 (4th June 2018) - Ma, Cuiping; Liu, Hefu; Gu, Jibao; Dou, Junsheng
Abstract : Purpose: The purpose of this paper is to focus on the cultural cognition of Chinese Zhong-yong thinking, which is deeply rooted in Chinese Confucius culture, and to examine how entrepreneurs' Zhong-yong thinking is related to new venture performance through guanxi network, and also examine how environmental turbulence affects the influencing mechanism. Design/methodology/approach: This paper follows an empirical design. Data are collected from a survey administered to entrepreneurs in new ventures of China. Regression analysis is used to test the hypothesis. Findings: Results show that entrepreneurs' Zhong-yong thinking is positively related to guanxi and new venture performance, and guanxi mediates the relationship between entrepreneurs' Zhong-yong thinking and new venture performance. In addition, environmental turbulence moderates the relationship between entrepreneurs' Zhong-yong thinking and guanxi such that the relationship is stronger under higher technological turbulence or lower market turbulence. Research limitations/implications: This research uses cross-sectional data, so causal conclusions cannot be made. In addition, more moderators should be considered. Practical implications: The present study enriches the understanding of how entrepreneurs' Zhong-yong thinking affects new ventures, which helps entrepreneur understand how to strategize according to external environment and develop what kind of cognitive style to deal with complex situation of their own venture. Originality/value: This study is a pioneer in exploring non-Western cognitive style– Zhong-yong thinking in entrepreneurial context. It not only enriches the understanding of how Chinese wisdom affects organizational strategy and organizational performance but also advances the cognition research in the field of entrepreneurship.